The effect of kelulut honey on clinical, inflammatory and immunological response in patients undergoing lower gastrointestinal surgery: a pilot study - Isa, Mohammad Izwan Mohd (2023)
Background: Kelulut honey is a type of honey produced by stingless bee. It exhibits anti-inflammatory and anti-oxidant properties and consists of fructose, glucose and trehalulose. These properties could potentially lessen the inflammatory response after surgery. To date, there is no clinical study conducted specifically to assess the effect of Kelulut honey in patients undergoing lower gastrointestinal surgery. Method and Material: We conducted a pilot study involving 42 participants undergoing lower gastrointestinal surgery. Participants were randomised into Kelulut honey and Carborie (control) group. Participants were required to consume 500-ml study beverage equivalent to 235 Kcal, 3 times daily on post-operative days 1 and 2. Primary endpoints were the time of first flatus and first bowel evacuation and CRP level on admission, 12th, 36th, 60th and 96th hour post-operatively. CBS was monitored in diabetic patients. Secondary endpoints were incidence of nosocomial infection, SSI and length of stay. Results: 2 participants withdrew before the surgery, leaving only 40 participants with equal size group. First flatus was reported after 28.5 hours and 37.0 hours post-operatively in Kelulut honey and Carborie group respectively. This difference was not statistically significant (P= 0.493). First bowel evacuation occurred earlier in Kelulut honey group at 47.92 hours, while that of control was at 65.78 hours post-operatively. This difference is not statistically significant (P=0.180). Serial CRP level measurement on 12th, 36th, 60th and 96th hour post-operatively was lower in the Kelulut honey group as compared to that of control, however it was not statistically significant. (P= 0.246, 0.884, 0.937, and 0.730). There was no difference demonstrated in incidence of nosocomial infection, SSI and length of stay. 15% of diabetic participants (n=11) in Kelulut honey group had persistent hyperglycaemia until day 4. Conclusion: Oral consumption of Kelulut honey after lower gastrointestinal surgery is safe. While there was no significant difference observed in between 2 groups, further study with larger sample size would be required to associate Kelulut honey with lower CRP levels.